The canning season - Horvath, Polly (Farrar Straus Giroux, 2005)
Thirteen-year-old Ratchet spends a summer in Maine with her eccentric great-aunts Tilly and Penpen, hearing strange stories from the past and encountering a variety of unusual and colorful characters.